Glycogen storage disease type Ia misdiagnosed as multiple acyl-coenzyme A dehydrogenase deficiency by mass spectrometry - Du, Juan; Dou, Li-Min; Jin, Yong-Hong; Wen, Qing-Fen; Lin, Ya-Fen; Wang, Jian-She (Frontiers in Pediatrics, 2022)
Objective To report a case of glycogen storage disease (GSD) type Ia misdiagnosed as multiple acyl-coenzyme a dehydrogenase deficiency (MADD) by mass spectrometry. Methods A 7 months old boy was admitted to our hospital for elevated transaminase levels lasting more than 1 month. His blood biochemistry showed hypoglycemia, metabolic acidosis, hyperlipidemia, elevated lactate and uric acid, elevated alanine amino transferase (ALT), aspartate amino transaminase (AST) and gamma-glutamyl transferase (GGT). Mass spectrometry analysis of blood and urine showed elevated blood acylcarnitines and dicarboxylic aciduria, indicating multiple acyl-coenzyme A dehydrogenase deficiency. Sanger sequencing of all exons of glucose-6-phosphatase (G6Pase) and electronic transfer flavoprotein dehydrogenase (ETFDH) was performed for the patient and his parents. Results Coding and flanking sequences of the G6Pase gene detected two heterozygous single base substitutions in the boy. One variant was in exon 1 (c.209G>A), Which was also detected in the father. Another was in exon 5 (c.648G>T), which was detected in the mother. Coding and flanking sequences of the ETFDH gene revealed no pathogenic/likely pathogenic variants in the boy. Conclusion GSD Ia can manifest elevated blood acyl carnitines and dicarboxylic aciduria which were the typical clinical manifestations of MADD. So the patient with clinical manifestations similar to MADD is in need of differential diagnosis for GSD Ia. Genetic testing is helpful to confirming the diagnosis of inherited metabolic diseases.